2017
DOI: 10.1016/j.neuropharm.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic glutamate receptors in cancer

Abstract: Metabotropic glutamate receptors (mGluRs) are widely known for their roles in synaptic signaling. However, accumulating evidence suggests roles of mGluRs in human malignancies in addition to synaptic transmission. Somatic cell homeostasis presents intriguing possibilities of mGluRs and glutamate signaling as novel targets for human cancers. More recently, aberrant glutamate signaling has been shown to participate in the transformation and maintenance of various cancer types, including glioma, melanoma skin can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 105 publications
0
40
0
1
Order By: Relevance
“…Group III mGluR is involved in malignancy of a lot of cancers [47]. The implication of mGluR7 in tumor formation has yet to be characterized [46].…”
Section: Glutamate As a Growth Factor For Glioblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…Group III mGluR is involved in malignancy of a lot of cancers [47]. The implication of mGluR7 in tumor formation has yet to be characterized [46].…”
Section: Glutamate As a Growth Factor For Glioblastomamentioning
confidence: 99%
“…In addition, mutations and single nucleotide polymorphisms (SNPs) of GRM1 were described in prostate cancer [61] and eight somatic variations of GRM1 were identified in cancers, including lung adenocarcinoma [62]. Group II mGluR is also implicated in a variety of cancer types [47], including melanoma [63]. Both group I and II mGluR are involved in glioma progression and the action in vitro and in vivo of agonists and antagonists of these receptors will be reported in detail in this review.…”
Section: Glutamate As a Growth Factor For Glioblastomamentioning
confidence: 99%
“…Consequently the activation of group II or III glutamate receptor membranes reduce cAMP formation [40,41]. Calcium and DAG activate protein kinase C, which, in turn, activates the MAPK and PI3K/AKT pathways which allow the upregulation of cell proliferation and anti-apoptosis signals [42]. Moreover; it has been observed that activated PI3K/AKT pathway functions in tumor cell by regulating; survival, angiogenesis and epithelial mesenchymal transition (EMT).…”
Section: Molecular Pathwaysmentioning
confidence: 99%
“…Calcium and DAG activate PKC, which, in turn, activates the MAPK and PI3K/AKT pathways allowing for the upregulation of cell proliferation and anti-apoptosis signals [21]. Additionally, activated PI3K/AKT pathway functions in tumor cell survival, epithelial mesenchymal transition (EMT), and angiogenesis.…”
Section: Melanoma Typesmentioning
confidence: 99%